Evaluation of the influence of formulation, food intake and species on voriconazole plasma concentration in birds - Burhenne, Jürgen (Veterinary medicine Austria, 2012)
Voriconazole is currently recommended as rst choice treatment for aspergillosis in birds. An evaluation of the in uence of food intake was performed with twelve African grey parrots. The birds received 10 mg/kg voriconazole orally in the morning after overnight fasting. Five days later, the same birds were treated with 10 mg/kg voriconazole in combination with 10 ml food. Blood was sampled from 0 to 12 hours after drug application. Further, a comparison of the commercially available suspension of voriconazole with suspended tablets was performed with two groups of pigeons. Blood was taken 90 minutes after drug administration. Compared species were African grey parrots (n=17), Amazon parrots (n=10), Macaws (n=4), racing pigeons (n=10), common kestrels (n=10) and common buzzards (n=10); all birds received 10 mg/kg voriconazole orally; blood was taken after 90 minutes.